Heavy ion irradiation effects on GaN/AlGaN high electron mobility transistor failure at off-state. (November 2019) - Islam, Zahabul; Paoletta, Angela L.; Monterrosa, Anthony M.; Schuler, Jennifer D.; Rupert, Timothy J.; Hattar, Khalid; Glavin, Nicholas; Haque, Aman
Abstract: We investigate the effects of ion irradiation on AlGaN/GaN high electron mobility electron transistors using in-situ transmission electron microscopy. The experiments are performed inside the microscope to visualize the defects, microstructure and interfaces of ion irradiated transistors during operation and failure. Experimental results indicate that heavy ions such as Au 4+ can create a significant number of defects such as vacancies, interstitials and dislocations in the device layer. It is hypothesized that these defects act as charge traps in the device layer and the resulting charge accumulation lowers the breakdown voltage. Sequential energy dispersive X-ray spectroscopy mapping allows us to track individual chemical elements during the experiment, and the results suggest that the electrical degradation in the device layer may originate from oxygen and nitrogen vacancies. Highlights: Gallium nitride based transistors were tested in a transmission electron microscope. Transistors were ion irradiated at up to 45 displacement/atom damage. Real-time degradation and failure microscopy showed proliferation of dislocations. Very high dislocation density led to high drain current on the onset of failure. Oxidation and generation of nitrogen vacancy was observed during failure.